Secretion of pro‐angiogenic extracellular vesicles during hypoxia is dependent on the autophagy‐related protein GABARAPL1. Issue 14 (2nd December 2021) - Keulers, Tom G.; Libregts, Sten F.; Beaumont, Joel E.J.; Savelkouls, Kim G.; Bussink, Johan; Duimel, Hans; Dubois, Ludwig; Zonneveld, Marijke I.; López‐Iglesias, Carmen; Bezstarosti, Karel; Demmers, Jeroen A.; Vooijs, Marc; et al.
Abstract: Tumour hypoxia is a hallmark of solid tumours and contributes to tumour progression, metastasis development and therapy resistance. In response to hypoxia, tumour cells secrete pro‐angiogenic factors to induce blood vessel formation and restore oxygen supply to hypoxic regions. Extracellular vesicles (EVs) are emerging as mediators of intercellular communication in the tumour microenvironment. Here we demonstrate that increased expression of the LC3/GABARAP protein family member GABARAPL1, is required for endosomal maturation, sorting of cargo to endosomes and the secretion of EVs. Silencing GABARAPL1 results in a block in the early endosomal pathway and impaired secretion of EVs with pro‐angiogenic properties. Tumour xenografts of doxycycline inducible GABARAPL1 knockdown cells display impaired vascularisation that results in decreased tumour growth, elevated tumour necrosis and increased therapy efficacy. Moreover, our data show that GABARAPL1 is expressed on the EV surface and targeting GABARAPL1 + EVs with GABARAPL1 targeting antibodies results in blockade of pro‐angiogenic effects in vitro. In summary, we reveal that GABARAPL1 is required for EV cargo loading and secretion. GABARAPL1 + EVs are detectable and targetable and are therefore interesting to pursue as a therapeutic target.